Pelaksanaan Peraturan Pemerintah Nomor 48 Tahun 2008 Tentang Pendanaan Pendidikan Terkait Pungutan Sekolah Pada Sekolah Menengah Negeri Di Medan - Jimmy Carter A.; Madiasa Ablisar; Marlina Marlina; Edy Ikhsan (Universitas Sumatera Utara, 2019)
Abstract. The legal basis for implementing levies is Article 51 PP Nmor 48 of 2008 number (5) letter c No 48 of 2008 concerning Education Funding which must follow the provisions stipulated in Article 52 of Government Regulation Number 48 of 2008 concerning Education Funding. Levies outside the provisions of legislation constitute illegal levies that have criminal sanctions depending on the case by case that occurs. The forms of levies in State High Schools in Medan are called School Fees or often called SPP in accordance with Government Regulation No. 48 of 2008. Some Medan Senior High Schools are still carrying out levies outside of school fees such as Research, School Sports Week, Christmas Money, Retreats, Study Tours , Qurban, Teacher's Day, Pool Money, LKS book money, Class Cash, Principal Cup, Farewell, etc. PP 48 of 2008 has not been fully implemented in the State High School in Medan. The implementation of PP 48 of 2008 is still experiencing problems, namely chaos that occurs during meetings / deliberations between Schools, School Committees, and other stakeholders. Keywords : education funding, levies